Enhancing Prednisone-Based Arthritis Therapy with Targeted IL-27 Gene Delivery - Adriana A. Marin; Richard E. Decker; Shreya Kumar; Zachary Lamantia; Hiroki Yokota; Todd Emrick; Marxa L. Figueiredo (Bioengineering, 2022)
Rheumatoid arthritis (RA) is a chronic autoimmune disease which is characterized primarily by synovial hyperplasia and accumulation of several types of immune infiltrates that promote progressive destruction of the articular structure. Glucocorticoids are often prescribed to treat RA because of their strong anti-inflammatory and immunosuppressive effects. However, their application must be limited to the short-term due to a risk of adverse events. In the present study, we examined the potential combination of low-dose prednisone with gene delivery of an agent of promising and complementary effectiveness in RA, interleukin (IL)-27. IL-27 has been shown to have anti-inflammatory potential, while also acting as an effective bone-normalization agent in prior reports. The present report examined a version of IL-27 targeted at the C-terminus with a short ‘peptide L’ (pepL, LSLITRL) that binds the interleukin 6 receptor α (IL-6Rα) upregulated during inflammation. By focusing on this targeted form, IL-27pepL or 27pL, we examined whether the anti-inflammatory potential of prednisone (at a relatively low dose and short duration) could be further enhanced in the presence of 27pL as a therapy adjuvant. Our results indicate that 27pL represents a novel tool for use as an adjuvant with current therapeutics, such as prednisone, against inflammatory conditions.